Association between bodyweight perception, nutritional status, and weight control practices: A cross-sectional analysis from the Chilean Health Survey 2016–2017 - Nazar, Gabriela; Alcover, Carlos-María; Lanuza, Fabián; Labraña, Ana María; Ramírez-Alarcón, Karina; Troncoso-Pantoja, Claudia; Leiva, Ana María; Celis-Morales, Carlos; Petermann-Rocha, Fanny (Frontiers in Psychology, 2022)
This research aimed (1) to examine the agreement between body mass index (BMI)-based nutritional status and perceived nutritional status overall and by socio-demographic factors and (2) to state the association between the accuracy of weight perception and weight control practices in the Chilean adult population. A population-based cross-sectional study was carried out with 5,192 Chilean adult participants from the Chilean National Health Survey 2016–2017. Agreement between BMI-based weight status and body weight perception for the total sample and across subgroups was determined using the weighted kappa coefficient. The agreement between BMI-based and perceived nutritional status of the total sample was fair (kappa = 0.38). A higher rate of weight perception accuracy was identified in women, younger respondents, and participants with higher education, a higher income, and from urban areas than their counterparts. Respondents with overweight or obesity tended to underestimate their nutritional status. Actions to lose weight were higher in those who had the right perception of their overweight/obesity condition and those who overestimated their body weight, regardless of their nutritional status. In all groups, weight loss behaviors were more related to the perceived than the BMI-based nutritional status. The consequences of accurate perception of the nutritional status are discussed including its effects on body weight and mental health.